INVESTIGATION OF DUSTY PARTICLE CHARGING PROCESS IN DC DISCHARGE SETUP - Amangaliyeva, R.Zh. (Recent Contributions to Physics, 2008)
The results of research of dusty particle charge’s radial distribution and charging time are presented. The data of this work allow concluding, that in stratum there are areas, where the charge of dusty particles grows with distance from an axis of tube. It is shown, that the characteristic of particle’s charging time is mainly determined by fluxes of ions on a particle surface.